The tribes of Desht-i-Kypchak: totemic meanings in ethnonyms - Stepanov, Е.Н.; Kairzhanov, А.К.; Ilyasova, З.С.; Akhmetova, Ж.Е. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The article considers the ethnonymy of Polovtsian field (altynoba, saryoba, arslanoba,ayopa, kitayoba, yetiyoba( itoba), chenegrepa, kyuchoba, kolobichi, toksoba, urusoba, berendechi, ulichi, torki), the tribal composition of which has different names in the Great Steppe such as Kipchaks, Polovtsy, Cumans (komans). There were formed methods and techniques of comparativists and hermeneutics, semantic analysis, and some techniques of the comparative historical method and synergetics are used to determine how certain Kipchak ethnonyms with a totemic component. The article reveals the semantics of totemic components of ethnonyms. The authors determined their reflexes and rudiments reflecting the ancient mythology of the nomads of the primitive era. In addition, there are analyzed some symbols imprinted in patterns and ornaments on some clothes of the Kipchak peoples. The article considers zoomorphic images of Kipchaks, and it is revealed that these images are equipollent with similar images of other ethnic groups, and at the same time, it is determined that they form part of the universal culture of the peoples of Eurasia.